Ellis Island : doorway to freedom - Kroll, Steven; Ritz, Karen (New York : Holiday House, 1995)
Describes how the immigration station on Ellis Island served as a gateway into the United States for more than sixteen million immigrants between 1892 and 1954.
Includes index.
850
850
Accelerated Reader AR
Keywords: Ellis Island Immigration Station (N.Y. and N.J.) -- History -- Juvenile literature; Ellis Island Immigration Station (N.Y. and N.J.) -- History; United States -- Emigration and immigration -- Juvenile literature; United States -- Emigration and immigration